Water polo shooting performance: Differences between world championship winning, drawing and losing teams - Canossa, S.; Abraldes, J. A.; Estriga, L.; Fernandes, R. J.; Garganta, J. (Journal of Human Kinetics, 2020)
Shooting performance of globally ranked winning, drawing and losing water polo teams was compared, and technical and tactical success indicators were identified. In total, 886 shots from a world championship final round werevideotaped and teams were clustered for a performance evaluation (considering differences between game outcomes). Shooting speeds were assessed by a radar, with higher values observed at further distances from the goal than in the central area close to the goal (p = 0.00, ES: 2.54). Shots tended to be more frequent from the central corridor, with =50% and >75% relative shot efficacy attained from field areas 3 and 6; winning teams obtained better results. Furthermore, winners had greater success than losers when shooting from field area 2 (p = 0.04, ES: 1.13) and towards the goal zone 2 (p < 0.03, ES: 1.10). They also attained better efficacy regarding shots towards goal zone 1, had better efficacy on the part of centre-forwards (p = 0.05, ES: 0.85-1.27), and were more effective regarding shots without a frontal defensive block. In addition, contingency analysis highlighted shots performed from field area 6, without a defensive block, toward the bottom left goal corner, and through man-up play as success indicators (all for p = 0.005). We concluded that world-level winning teams homogeneously distributed their shot opportunities at the second offensive line with balanced efficacy, creating variability and uncertainty in their opponents` defensive action. Elite level players must be capable of interpreting game situations with intelligence and proper decision making. This information may be useful for improving teams performance.